2011
DOI: 10.1016/j.cpc.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

OPUCEM: A library with error checking mechanism for computing oblique parameters

Abstract: After a brief review of the electroweak radiative corrections to gauge-boson self-energies, otherwise known as the direct and oblique corrections, a tool for calculation of the oblique parameters is presented. This tool, named OPUCEM, brings together formulas from multiple physics models and provides an error-checking machinery to improve reliability of numerical results. It also sets a novel example for an "open-formula" concept, which is an attempt to improve the reliability and reproducibility of computatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Although the off-diagonal lepton mixings are required to be smaller than 0.115 to be consistent with the recent global fits [20], a trivial 4 × 4 PMNS unitary matrix is considered throughout this analysis, namely a long-lived Dirac neutrino with |U ν τ | = 1. We mention, however, the interest of the Majorana case, as the exhaustive study [21] has shown.…”
Section: Direct Limitsmentioning
confidence: 95%
“…Although the off-diagonal lepton mixings are required to be smaller than 0.115 to be consistent with the recent global fits [20], a trivial 4 × 4 PMNS unitary matrix is considered throughout this analysis, namely a long-lived Dirac neutrino with |U ν τ | = 1. We mention, however, the interest of the Majorana case, as the exhaustive study [21] has shown.…”
Section: Direct Limitsmentioning
confidence: 95%
“…These S, T, U parameters can be defined in both unphysical and physical gauge boson basis as [66,70,221,222]:…”
Section: Oblique Parametersmentioning
confidence: 99%
“…The existence of the fourth SM family is the outcome of the flavor democracy hypothesis and the actual spectrum of the third family fermion masses [4][5][6] (see, also review [7] and ref's therein). Twenty years' ongoing discussions on "precision data vs fourth SM family" have been concluded in favor of the fourth SM family (see [8,9] and ref's therein). Today, the mass and the mixing patterns of quarks and leptons are the most mysterious aspects of particle physics.…”
mentioning
confidence: 99%